Integrated of Geographic Information System for Supporting Tourism 12 Cities Hidden Gems Plus: Case Study Eastern Region - Kittisirisawat, Krissanee; Ngamjaroensoktavorn, Patcharaporn; Junkaew, Nutthapol (Journal of Applied Informatics and Technology, 2023)
The aim of this research is to provide a geographic information system on the tourism 12 Cities Hidden Gems plus provincial groups on patrol routes, educational routes, tourist attractions and facilities, and tourist attractions in a sequence of steps in the form of online media on Google Maps. This research used network analysis, considering the distance and time for traveling. There is invent the database of geographic information and maps to show the position of tourist attractions 55 places, 325 places of hotels, 248 places of restaurants, 59 places of police stations, and 40 places of hospitals. The result of the routes analysis is divided into routes from the main road that entrance to the eastern region to Chanthaburi, Sakae, Trat, and Rayong The route takes the most time and distance is highway no.304 to Trat city hall takes 5 hours 13 minutes, distance 295.9 kilometers. The route takes the shortest time and distance is Highway no.304 to Sakaew city hall takes 1 hour 49 minutes, a distance of 92.1 kilometers. And routes from tourist attractions of couple provinces to the other that same type of tourist attractions. There are 8 routes that are divided into 3 routes for Chanthabiri to Sakaew and 5 routes for Trat to Rayong. The result of service area analysis for tourist attractions that can arrive in 15, 30, and 45 minutes. There are 23 places of tourist attractions divided into 6 places of Chanthabiri, 5 places of Sakaew, 6 places of Trat, and 5 places of Rayong. The result of closest facility analysis shows the best routes from 23 places of tourist attractions to closest facility, namely 325 places of hotels, 248 places of restaurants, 59 places of police stations, and 40 places of hospitals. There is a public database of geographic information about tourist attractions of 12 Hidden Gems Plus campaign and facilities, namely hotels, restaurants, police stations, hospitals, orchards, and souvenir shops covering provinces in the eastern region on Gmail account 12Cities.plus@gmail.com in form of online media Google Maps to interested persons or related organizations. Those who are interested can use the GIS database prepared to be used for further research. And was inspired to continue to bring the application of GIS It has been used to support tourism in Tourism 12 Cities Hidden Gems Plus in other regions and related agencies can use the research results to support tourism " Tourism 12 Cities Hidden Gems Plus" in the eastern region. And this research has been extended to be prepared in various languages ​​such as English, Chinese, etc. to benefit and convenience for foreign tourists.